PERANAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Ginting, Rahmadani Fitri; Rati, Agieasta Sera (Cahaya Ilmu Bangsa Institute, 2024)
The role of teachers in enhancing student learning motivation is one of the integral activities that must be present in the learning process. In addition to providing and transferring knowledge, teachers are also tasked with improving students' motivation to learn. It is undeniable that each student has different learning styles, making it essential for teachers to continuously motivate students to maintain a strong spirit of learning. With good motivation, students are expected to become outstanding individuals and develop themselves optimally. The learning process will succeed if students possess strong motivation. Therefore, teachers need to foster optimal student motivation. Teacher creativity in creating an engaging learning environment is crucial for stimulating student motivation. Learning motivation is related to the meaning, value, and benefits of learning activities that are interesting for students Peranan guru dalam meningkatkan motivasi belajar siswa merupakan salah satu kegiatan integral yang harus ada dalam proses pembelajaran. Selain memberikan dan mentransfer pengetahuan, guru juga memiliki tugas untuk meningkatkan motivasi siswa dalam belajar. Tidak dapat dipungkiri bahwa setiap siswa memiliki cara belajar yang berbeda, sehingga penting bagi guru untuk terus memotivasi agar siswa memiliki semangat belajar yang tinggi. Dengan motivasi yang baik, siswa diharapkan dapat menjadi individu yang unggul dan mampu mengembangkan diri secara optimal. Proses pembelajaran akan berhasil jika siswa memiliki motivasi yang kuat. Oleh karena itu, guru perlu mengembangkan motivasi belajar siswa secara optimal. Kreativitas guru dalam menciptakan suasana belajar yang menarik sangat diperlukan untuk membangkitkan motivasi siswa. Motivasi belajar berkaitan dengan makna, nilai, dan manfaat dari kegiatan pembelajaran yang menarik bagi siswa.